DETEKSI CEMARAN TOTAL BAKTERI DAN IDENTIFIKASI Salmonella sp. PADA TELUR GARAM YANG DIJUAL DI PASAR TRADISIONAL DI DENPASAR BALI : DETECTION OF TOTAL BACTERIAL CONTAMINATION AND IDENTIFICATION OF Salmonella sp. ON SALT EGGS SOLD AT THE TRADITIONAL MARKET IN DENPASAR BALI - Marieta Demarilac Dimung; Ni Made Susun Parwanayoni; Dwi Ariani Yulihastuti (Program Studi Biologi Universitas Udayana, 2025)
ABSTRACT Salt eggs are a type of egg that undergoes a five-hour boiling process and then coated with salt. Eggs are subject to damage, both from external sources and during microbial development. One of the microorganisms that contaminate eggs is Salmonella sp. This study aims to identify Salmonella sp. and examine the detection of total bacterial contamination in salted eggs sold in traditional markets in Denpasar Bali. Samples of this study were taken from 10 traditional markets located in Denpasar Bali randomly and three times repeated. The type of research conducted is descriptive research which describes the total bacteria in salt eggs and the presence or absence of Salmonella sp. The data collected is displayed using tables, figures, and in-depth explanations based on the findings of relevant literature reviews. Based on the results of the Alt test, it shows that at a dilution of 10-3 salt egg samples from Peguyangan and Kertha Boga Pemogan markets have more than 300 colonies (TBUD). This number still meets the SNI requirements, which is a maximum of 1 x 105 CFU. The results of the Salmonella sp. bacteria detection test are that all salt egg samples are free of Salmonella sp. bacteria.